Recurrence pattern and outcomes in T4 colon cancer: A single institution analysis. Issue 2 (14th November 2019) - Macari, David; Kawak, Samer; Raofi, Vandad; Wasvary, Harry; Jaiyesimi, Ishmael
Abstract: Background and objectives: Patients with T4 colon adenocarcinoma have an increased risk of locoregional and distant recurrence. This study defines the metastatic pattern, predictors of recurrence, and efficacy of adjuvant treatment in T4 colon cancer. Methods: A retrospective review was performed of patients with T4 colon adenocarcinoma from May 2005 to November 2015 at a tertiary care hospital. Baseline factors, follow‐up, recurrence, and survival were collected and analyzed. Results: Locoregional recurrence (LR) rates for N0, N1, and N2 were 21/85 (24.7%), 14/50 (28%), and 21/46 (45.7%), respectively ( P  = .014). Multivariate analysis for distant recurrence was significant for positive nodes (hazard ratio [HR], 3.3; 95% confidence interval [CI], 1.1‐9.9). Multivariate analysis for LR was significant for the following variables: perforation (HR, 2.7; 95% CI, 1.2‐6.2), lymphovascular invasion (HR, 2.7; 95% CI, 1.1‐6.7), positive nodes (HR, 2.8; 95% CI, 1.2‐6.9), and positive margins (HR, 5.0; 95% CI, 2.1‐12.1). Multivariate analysis for overall survival was significant for: signet ring histology (HR, 2.5; 95% CI, 1.2‐5.8), positive nodes (HR, 2.3; 95% CI, 1.2‐4.4), and positive margin (HR, 2.8; 95% CI, 1.4‐5.8). Conclusion: T4 colon adenocarcinoma has a high risk of LR and mortality. Clinical trials utilizing the aforementioned high‐risk features may increase the ability to demonstrate beneficial intervention.